PVTSim Prediction of Hydrate Phase Equilibrium of a Modified Natural Gas Composition in Sabah Operation Sumandak-Bravo Field (SUPGB) - Ting, Vennesa Johnny (IRC, 2016)
Gas hydrates are vast potential energy resources that can be used for gas storage and transportation. Under low temperature and high pressure conditions, gas hydrate can easily form inside subsea and production pipelines, causing flow assurance and safety issues in the oil and gas industry. Therefore, it is crucial to study the effect of each variable in the natural gas system by analyzing the hydrate phase equilibrium to ascertain the best way to mitigate hydrate formation.